2015
DOI: 10.1016/j.jbtep.2014.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a brief 4-session psychoeducation procedure for high worriers based on the mood-as-input hypothesis

Abstract: Given the ubiquity of worrying as a consuming and distressing activity at both clinical and sub-clinical levels, it is important to develop theory-driven procedures that address worrying and allow worriers to manage this activity. This paper describes the development and testing of a psychoeducation procedure based on mood-asinput hypothesis, which is a transdiagnostic model that describes a proximal mechanism for perseverative worrying. The study used nonclinical participants meeting IAPT criteria indicating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Psychoeducation can also be effective for non-clinical issues. For example, research has shown that psychoeducation reduces irrational beliefs, stress and worry (Dash et al, 2015; Ulusoy & Duy, 2013; Van Daele et al, 2012). In particular, a meta-analysis of 17 studies demonstrated that interventions providing information about stress and diverse techniques to respond to stress effectively can reduce worry for people of different gender, age and ethnicity (Van Daele et al, 2012).…”
Section: Could Psychoeducation Promote Self-compassion?mentioning
confidence: 99%
“…Psychoeducation can also be effective for non-clinical issues. For example, research has shown that psychoeducation reduces irrational beliefs, stress and worry (Dash et al, 2015; Ulusoy & Duy, 2013; Van Daele et al, 2012). In particular, a meta-analysis of 17 studies demonstrated that interventions providing information about stress and diverse techniques to respond to stress effectively can reduce worry for people of different gender, age and ethnicity (Van Daele et al, 2012).…”
Section: Could Psychoeducation Promote Self-compassion?mentioning
confidence: 99%
“…Results of this study showed that this brief, low-intensity and low-cost procedure significantly reduced worry scores in a group of highly anxious students. Although the dependent variable of our studies (being level of task persistence) is different than that used in the study of Dash et al, 2014, (being level of worrying) a psycho-educational intervention program could be developed for pain, based on their results. The goal of the intervention would be to provide insight into the relative importance of pain-avoidance as well as achievement goals and to focus on the adoption of a flexible goal pursuit style.…”
Section: Discussionmentioning
confidence: 99%